Myocarditis and sports in the young: data from a nationwide registry on myocarditis—"MYKKE-Sport" - Schöffl, I.; Holler, S.; Dittrich, S.; Pickardt, T.; Opgen-Rhein, B.; Boehne, M.; Wannenmacher, B.; Reineke, K.; Wiegand, G.; Hecht, T.; Kaestner, M.; Messroghli, D.; et al. (Frontiers in Sports and Active Living, 2023)
Background: Myocarditis represents one of the most common causes of Sudden Cardiac Death in children. Myocardial involvement during a viral infection is believed to be higher as a consequence of intensive exertion. Recommendations for return to sports are based on cohort and case studies only. This study aims to investigate the relationship between physical activity and myocarditis in the young.